2021
DOI: 10.1177/21582440211006387
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Antecedents of User Donation Intentions Toward Social Media Articles: Moderation Effects of Social Contagion

Abstract: Donations to articles on social media, as a new behavior, have been trending in recent years. Unlike donations to a charitable and nonprofit organization or victims, donations to social media articles have been accorded minimal attention from academic researchers. From the stimuli–organism–response framework, this study proposed a model to investigate the factors that influence the donation intentions of users on social media toward articles. Our results demonstrate that the credibility of the article determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…(Xu et al, 2020) Social interaction stimuli, such as review quality, source credibility, and observational learning, perceived usefulness, positive affect, impulse buying, and impulse buying behavior, are related to each other. This also supports the findings of (Asante et al, 2021) where source credibility has a significant impact on PU. The results state that source credibility positively affects perceived usefulness.…”
Section: H3supporting
confidence: 89%
See 1 more Smart Citation
“…(Xu et al, 2020) Social interaction stimuli, such as review quality, source credibility, and observational learning, perceived usefulness, positive affect, impulse buying, and impulse buying behavior, are related to each other. This also supports the findings of (Asante et al, 2021) where source credibility has a significant impact on PU. The results state that source credibility positively affects perceived usefulness.…”
Section: H3supporting
confidence: 89%
“…Source credibility has a positive and significant impact on perceived usefulness in the context of mobile shopping apps (Vo & Wu, 2022). Source credibility has a significant impact on perceived usefulness, which in turn affects intentions (Asante et al, 2021).…”
Section: H2mentioning
confidence: 99%
“…The popularity of social media lies in the extended social relationships through Internet. It is also one of the main reasons people choose peer‐to‐peer fundraising over traditional intermediaries (e.g., Asante et al, 2021; Bhati & McDonnell, 2020). To fully understand the mechanism for social media fundraising, one needs to take a closer look at the influence of social relationships.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In comparison, individuals are more likely to trust personal sources within their own social circles. As a result, social media has begun to play an important role in charitable giving because of its easy access and massive social connections (e.g., Asante et al, 2021; Bhati & McDonnell, 2020; Saxton & Wang, 2014). Research suggested that social interactions through digital media have powerful impact on online giving behaviors (Saxton & Wang, 2014; Scharf & Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%